REDD+ as an international law mechanism of world forest ecosystem protection in the developing coun-tries - Яцухненко, Євгеній Сергійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The author analyzes some aspects of the development and implementation of the mechanisms of Reducing Emissions from Deforestation and Forest Degradation and their effectiveness for the global forest ecosystems protection and the achieving of stable development in the developing countries. REDD + can be considered as a mechanism of international legal protection of the forest ecosystems, because legally it is a set of tools and methods for management and implementation of the international relations, directly or indirectly related to the protection of the forest ecosystems in developing countries. The basis for its introduction is the international legal regime for the prevention of climate changes.